Drivers to implement a chatbot as a new channel for customer service in Peruvian financial entities - Yshikawa Kobayashi, Tatiana Lucía (2022)
Adopting chatbots as an additional user service channel in companies has been an essential source of savings in companies, and its adoption has increased at least during the last ten years. In addition, due to the leading global restriction of avoiding human contact caused by the COVID-19 pandemic, industries accelerated the launching of projects associated with digitization. In Peru, the banking sector also emphasized this channel, mainly because of a digital transformation trend. Customer Service was restricted to a reduction of at least 50% of the capacity in the agencies and reduced opening hours. On the other hand, in the insurance sector, the demand for consultations increased due to the medical assistance cases to be attended. In short, the call center channel was more saturated than in average levels of service. However, except for this atypical period, the users prefer to avoid using this channel, even though financial entities continue to bet on it. This research will identify the main drivers for implementing a chatbot, starting with some surveys of financial institution users in the Peruvian market to support their level of satisfaction with the use of the tool. Then, through interviews with experts, different selection and grouping methods may be used to arrive at a final classification.